Anthropogenic and Natural Radiative Forcing: Positive Feedbacks - Jean-Louis Pinault (Journal of Marine Science and Engineering, 2018)
This article is based on recent work intended to estimate the impact of solar forcing mediated by long-period ocean Rossby waves that are resonantly forced—the ‘Gyral Rossby Waves’ (GRWs). Here, we deduce both the part of the anthropogenic and climate components within the instrumental surface temperature spatial patterns. The natural variations in temperature are estimated from a weighted sum of sea surface temperature anomalies in preselected areas of subtropical gyres representative of long-period GRWs. The temperature response to anthropogenic forcing is deduced by subtracting the climate component from the instrumental temperature. Depending on whether the inland regions are primarily impacted by latent or sensible heat fluxes from the oceans, positive feedbacks occur. This suggests that the lapse rate and the high troposphere cloud cover have a driving role in the amplification effect of anthropogenic climate forcing, while specifying the involved mechanisms.